Temporal dynamics of gene and protein signatures following volumetric muscle loss - Jain, Ishita; Oropeza, Beu P.; Hu, Caroline; Chiang, Gladys; Aravindan, Sree; Reyes, Renato; Li, Daniel Yuhang; Cheng, Paul; Huang, Ngan F. (Frontiers in Cell and Developmental Biology, 2025)
IntroductionVolumetric muscle loss (VML) is characterized by permanent tissue impairment resulting from critically-sized muscle loss. We performed time-series transcriptomic and proteomic analyses to reveal key mediators of irreversible pathological remodeling after induction of VML in mice.MethodsThe dynamics of gene and protein expression patterns were analyzed for up to 3 weeks after muscle injury.ResultsRNA Sequencing revealed transcriptional patterns that show rapid upregulation or downregulation shortly after injury, among which a subset of genes failed to return to pre-injury levels within 3 weeks after VML. Time-series analysis revealed gene clusters with sustained upregulation after 3 weeks, including those associated with extracellular matrix remodeling and inflammation, whereas the gene clusters having sustained downregulation were associated with mitochondrial function and metabolism. We further identified SPI1 and SP1 as novel molecular mediators of the pathological remodeling process.DiscussionThis work demonstrates the utility of time-series analysis to reveal dysregulated pathways in the setting of VML.